Neuroligin-1 dependent phosphotyrosine signaling in excitatory synapse differentiation - Szíber, Zsófia; Drouet, Adèle; Mondin, Magali; Levet, Florian; Thoumine, Olivier (Frontiers in Molecular Neuroscience, 2024)
The synaptic adhesion molecule neuroligin-1 (NLGN1) is involved in the differentiation of excitatory synapses, but the precise underlying molecular mechanisms are still debated. Here, we explored the role of NLGN1 tyrosine phosphorylation in this process, focusing on a subset of receptor tyrosine kinases (RTKs), namely FGFR1 and Trks, that were previously described to phosphorylate NLGN1 at a unique intracellular residue (Y782). We used pharmacological inhibitors and genetic manipulation of those RTKs in dissociated hippocampal neurons, followed by biochemical measurement of NLGN1 phosphorylation and immunocytochemical staining of excitatory synaptic scaffolds. This study shows that: i) the accumulation of PSD-95 at de novo NLGN1 clusters induced by neurexin crosslinking is reduced by FGFR and Trk inhibitors; ii) the increase in PSD-95 puncta caused by NLGN1 over-expression is impaired by FGFR and Trk inhibitors; iii) TrkB activation by BDNF increases NLGN1 phosphorylation; and iv) TrkB knock-down impairs the increase of PSD-95 puncta caused by NLGN1 overexpression, an effect which is not seen with the NLGN1 Y782A mutant. Together, our data identify TrkB as one of the major RTKs responsible for NLGN1 tyrosine phosphorylation, and reveal that TrkB activity is necessary for the synaptogenic effects of NLGN1.